A New Mission for Schools in Hong Kong in the 21st Century: Promoting Effective KM - Esther Chan (Journal of Systemics, Cybernetics and Informatics, 2005)

(untitled)
Knowledge Management, though a hot topic in business, is quite a new concept in schools and in the education sector in Hong Kong. KM involves identifying, preserving, sharing and making the knowledge assets grow. Proper management of the knowledge assets will make the schools or educational organizations more responsive to changes and to operate successfully in the information age. Thus, there is a need to promote effective knowledge management in schools. The first section of the paper aims to define KM and the relationship of knowledge, information and data. The second section discusses some practical ways that lead to effective handling of knowledge in schools.